Is there any benefit with pantoprazole treatment in infantile hypertrophic pyloric stenosis? - Natasha Fourie; Marion Arnold; Behrouz Banieghbal; Samantha Lynn Marchant (Wolters Kluwer Medknow Publications, 2022)
Context: Previous studies demonstrated faster correction of metabolic derangement associated with hypertrophic pyloric stenosis with pre-operative intravenous (IV) histamine-2 receptor antagonists. Aims: We investigated if similar outcomes are achieved with IV pantoprazole, a proton-pump inhibitor (PPI), including the subgroup of delayed presenters in the South African setting. Settings and Design: A 5-year retrospective record review (January 2014-December 2018) compared the rate of metabolic correction in patients with hypertrophic pyloric stenosis at two tertiary centres. Subjects and Methods: One centre routinely administers IV pantoprazole (1 mg/kg daily) preoperatively (PPI group) and the other does not (non-PPI group). Fluid administration, chloride supplementation and post-operative emesis were evaluated. Statistical Analysis: Spearman's rank correlation coefficient was used to calculate statistical significance for discrete dependent variables. Continuous variables were compared between the groups using the Student t-test. Fisher's exact contingency tables were used to classify categorical data and to assess the significance of outcome between two treatment options. P < 0.05 was considered statistically significant. Results: Forty-two patients received IV pantoprazole and 24 did not. The mean time of metabolic correction was 8 h shorter in the PPI group (P = 0.067). Total pre-operative chloride administration correlated to the rate of metabolic correction in both cohorts (P < 0.0001). Profound hypochloraemia (chloride <85 mmol/l) was corrected 23 h faster in the PPI group (P < 0.004). Post-operative emesis was noted: 0.45 episodes/patient in the PPI group and 0.75 episodes/patient in the non-PPI group (P = 0.01). Conclusions: Pre-operative IV pantoprazole administration showed a faster correction of metabolic derangements, and in profound hypochloraemia, the correction occurred substantially faster in the PPI group. Post-operative emesis was significantly less frequent in the PPI group.